FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN LAPORAN KEBERLANJUTAN (Studi Empiris pada Perusahaan yang Terdaftar pada Bursa Efek Indonesia Periode 2018 - 2020) - Winda Wahyu Widowati; Siti Mutmainah (Diponegoro Journal of Accounting, 2023)
The rapid expansion of financial markets have an impact on increased investment activities. However, it is also accompanied by the risk of difficulty in obtaining reliable and accountable informations. Therefore, the stakeholders need financial reports and sustainability reports to find determine the company's performance from economic, environmental, and social aspects.This study aims to analyze the factors that can influence the disclosure of sustainability reports. The data used in this study is secondary data in the form of annual reports and sustainability reports issued by companies listed on the Indonesia Stock Exchange (IDX). This study uses purposive sampling as the sample selection method and multiple linear regression as the analytical method. A total of 56 companies were selected as the research sample from a total population of 825 companies during 2018-2020.The results of this study show that firm size and independent commissioners have positive and significant effect on the disclosure of sustainability reports. While other factors such as profitability, leverage, firm growth, and ownership structure have no effect on the disclosure of sustainability reports.